2017
DOI: 10.1186/s12885-017-3638-1
|View full text |Cite
|
Sign up to set email alerts
|

3,6-Dihydroxyflavone regulates microRNA-34a through DNA methylation

Abstract: BackgroundBreast cancer is the common cancer in China. In previous study, we determined that 3,6-dihydroxyflavone (3,6-DHF) increases miR-34a significantly in breast carcinogenesis, but the mechanism remains unclear.MethodsWe used qRT-PCR to analyze miR-34a and ten-eleven translocation (TET)1, TET2, TET3 levels in breast cancer cells. With a cellular breast carcinogenesis model and an experimental model of carcinogenesis in rats, TET1 levels were evaluated by western blot analysis and immunofluorescence. TET1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…Aberrant expressions of miRNAs are involved in the regulation of stemness in various cancers by controlling stemness-related gene expressions [10, 11, 14, 3440]. miR-34a has been recognized as a tumor-suppressive miRNA and reduced carcinogenesis in a variety of cancers, including OS [3033]. Underexpression of miR-34a has been implicated in maintaining the stemness of CSLCs [14, 15], especially in OS cells [10, 11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant expressions of miRNAs are involved in the regulation of stemness in various cancers by controlling stemness-related gene expressions [10, 11, 14, 3440]. miR-34a has been recognized as a tumor-suppressive miRNA and reduced carcinogenesis in a variety of cancers, including OS [3033]. Underexpression of miR-34a has been implicated in maintaining the stemness of CSLCs [14, 15], especially in OS cells [10, 11].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, tumor-suppressive miRNAs could be silenced by DNA hypermethylation in the promoter regions [2629]. Recent studies showed that miR-34a promoter hypermethylation led to epigenetic inactivation [3033]. Considering the regulation of stemness of OSLCs by miR-34a [10, 11], we hypothesized that it may be possible to repress the stemness by upregulating miR-34a through inactivating DNMT1 in human OS cells and their derived OSLCs.…”
Section: Introductionmentioning
confidence: 99%
“… Zhao et al (2017) also demonstrated that combined miR-34a mimics and EGFR-TKIs synergistically sensitized both EGFR wild-type and mutant NSCLC cells. The hypermethylation of miR-34a promotor was mediated by several DNA methyltransferases (Dnmts), including Dnmt1, Dnmt2, and Dnmt3a ( Peng et al, 2015 , 2017 ; Wang et al, 2016 ; Lewinska et al, 2018 ). Here, we show MIAT binds to the miR-34a promotor, and recruits Dnmt3a to methylate the promotor, leading to silencing of miR-34a expression.…”
Section: Discussionmentioning
confidence: 99%
“…DNMT1 is important in maintaining cancer stem cells since upregulated miR-34a associated with DNMT1 inhibition can reduce the viability of liver cancer cells [27]. We therefore initially explored whether CD133 + spheres from MHCC97H cells used as LCSCs are involved in DNMT activation and methylation silencing of miR-34a.…”
Section: Dnmt1 Activation Promotes the Stemness Of Lcscsmentioning
confidence: 99%